Recent results from OKA setup at U-70 synchrotron. (April 2020) - Obraztsov, V
Abstract: Several radiative decays are under study by OKA setup at U-70 synchrotron. First, the radiative decay K + → µ + νγ ( K µ 2 γ ) is studied on statistics of about 95K events for 25 MeV < E γ * < 150 MeV. A clear destructive interference between bremsstrahlung and structure dependent SD − term is observed. As a result, the vector and axial-vector form factors difference is measured: F V − F A = 0.134 ± 0.021( stat. ) ± 0.027( syst. ) which is 2.3 σ away from χ P T O ( p 4 ). Moreover, the decay K + → π + π − π + γ is studied on statistics of about 450 events for 30 Mev < E γ * < 70 Mev. The total and differential branching fractions of the decay are measured. Br( K + → π + π − π + γ ) = (7.1±0.4( stat. )±0.3( syst. ))·10 −6 to be compared with χ P T O ( p 4 ) (6.65 ± 0.05) · 10 −6 . In addition, a search for an up-down photon asymmetry with respect to the hadronic system decay plane is performed.